Key Determinants of Tuberculosis Prevention Behaviors Among Families in Indonesia: A Cross-Sectional Study Analysis - Hapiz Arlanda Sani; Anto J. Hadi; Herman Hatta (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Tuberculosis (TB) is one of the infectious diseases that is still a global health problem, including in Indonesia. TB prevention requires the active role of the family as the smallest unit of society to create a supportive environment. Studies of TB prevention behaviors in families are important to understand the factors influencing prevention success. Objective: This study analyzes factors related to TB prevention behavior in families. Methods: This study used a cross-sectional study design involving 129 families with family members with a history of TB in the Batunadua Health Center working area in Padangsidimpuan City, selected by purposive sampling. Data was collected through a structured questionnaire. Data analysis was conducted using the chi-square and logistic regression tests to see the relationship between the variables and the most meaningful variables. Results: This study found that knowledge about TB (p=0.001), access to health services (p=0.001), social and cultural environment (p=0.001), and personal health experiences (p=0.001) were related to TB prevention behavior in families. Meanwhile, the variable most related to TB prevention behavior is knowledge about TB Exp (B) = 46.888. Conclusion: This study concludes that TB prevention behavior in families is influenced by factors such as knowledge about TB, access to health services, social and cultural environment, and personal health experience, which have a significant relationship. Of the four variables, knowledge about TB is the most dominant factor influencing TB prevention behavior. Therefore, health education campaigns must be a priority, focusing on increasing family knowledge about TB through easily accessible media, such as counseling, social media, and pamphlets.